Contribution to the knowledge of Chinese Gryllacrididae (Orthoptera) V: Further study on the Chinese Capnogryllacris and comment on the phylogenetic relationships of the Gryllacrididae - Liu, Jing; Lu, Xiangyi; Zhang, Qianwen; Wu, Xiangyi; Yang, Dongdong; Bian, Xun (Zootaxa, 2022)
Based on the specimens deposited in Guangxi Normal University, the paper mainly deals with Capnogryllacris and reports one new species and four new subspecies, viz. Capnogryllacris sequestris Liu, Lu & Bian sp. nov. (Chinese name: 断纹烟蟋螽), Capnogryllacris erythrocephala maculates Liu, Lu & Bian ssp. nov. (Chinese name: 斑背烟蟋螽), Capnogryllacris nigromarginata hainanensis Liu, Lu & Bian ssp. nov. (Chinese name: 海南黑缘烟蟋螽), Capnogryllacris nigromarginata rectispina Liu, Lu & Bian ssp. nov. (Chinese name: 直刺黑缘烟蟋螽) and Capnogryllacris xichou flavifrons Liu, Lu & Bian ssp. nov. (Chinese name: 黄面西畴烟蟋螽). The next-generation sequencing technology was used to sequence the mitochondrial genomes of 13 specimens of Gryllacrididae, and the characteristics of newly obtained mitogenomes were introduced. The gene arrangements are completely consistent with other known orthopteran insects, and there is a long IGS of 166 bp–217 bp between trnK and cox2 genes in three individuals of C. erythrocephala maculatis ssp. nov.. Meanwhile, fourteen specimens of Capnogryllacris were delimited using COI barcode by constructing NJ tree and two distance-based barcoding methods (ABGD and jMOTU). Among the three methods, C. erythrocephala maculatis, C. rufonotata and C. spinosa can be correctly identified, but C. nigromarginata shows some differences in morphological and genetic distance, and Capnogryllacris melanocrania is divided into two clades. The Bayesian inference (BI) and Maximum likelihood (ML) trees based on the 13 protein-coding genes data supported the division of Gryllacrididae into two groups according to whether the male ninth abdominal tergite with median furrow or split along the midline or not.